Double standards: examples and exceptions in scientific metrological practices in Brazil. (May 2015) - Walford, Antonia; BANDAK, ANDREAS; HØJER, LARS
<x xml:space="preserve">Abstract</x> Drawing on fieldwork with metrologists from Brazil's Space Institute in the southeast of Brazil, this paper explores the science of measurement and calibration in terms of the relation between examples and exceptions. It argues that in order to understand how examples circulate in metrological practice in the form of versions of an absolute standard for a measurement, it is necessary to take into account how they appear as exceptions from that standard. The example and the exception emerge as forms of each other – neither opposed nor alike, but conveying the same information differently. The paper then turns to examine how this example of exemplification as exception can be methodologically engaged. If the introduction to this special issue proposes that 'their' examples are best thought of as 'our' examples, this paper ends with a discussion of how exactly metrological exemplification could come to be anthropological description.